IMPLEMENTACIÓN DEL SERVICIO MUNICIPAL DE ESTACIONAMIENTO TARIFADO EN LA CIUDAD DE ZAMORA (SMET-Z) Y SU IMPACTO EN LA MOVILIDAD URBANA: PERIODO DE ESTUDIO MAYO-AGOSTO 2016 - Montaño Villavicencio, Glenda Catalina (2017)
The present thesis entitled "Implementation of the Municipal Service of Tariff Parking in the City of Zamora (SMET-Z) and its Impact on Urban Mobility: study period May-August 2016", aims to analyze the existing problems in the Mobility of the city of Zamora from the implementation of SMETZ. The importance of the study of the implementation of the municipal parking fee service of the city of Zamora lies in the right to use the public road, in the center and the free fair through an organized and orderly way, avoiding agglomeration and facilitating. The access to a space to be parked to all who transit these zones. When carrying out this study work, it seeks to know the impact that this service generated in urban mobility, so that the managers know the effects and analyze their contribution from its implementation and in turn to show how the objectives have been met Raised by the institution; All with the aim of ensuring that the institution provides a better service which effectively contributes to urban mobility in the community. Finally, it is determined that the parking service has had a positive impact on urban mobility, being a key factor that allows the good movement of vehicles, provides the right to use the public way in an organized and orderly manner in addition to generating A permanent and continuous offer of spaces to park.